The effect of implementing remote work policies post-Covid-19 on private bank back office employees - Eki, Eki; Ramli, Abdul Haeba (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This 2023 study, employing the Structural Equation Model (SEM) method, delves into factors impacting remote work among back-office employees in private banks. Focusing on 205 respondents with a minimum of one year of experience, data collected through Google Forms reveals noteworthy findings. Attitude towards remote work positively affects concentration during remote work, subsequently enhancing remote work performance. Both built environment ICT and other enablers' availability, along with built environment facilities, contribute positively to remote work satisfaction. Moreover, remote work satisfaction positively correlates with remote work performance. However, the study indicates that the working conditions of a built environment do not significantly influence remote work satisfaction. The research underscores the managerial imperative of corporate governance tailored to the remote work engagement of back-office employees in private banks. Recognizing the significance of primary supportive tools, adequate facilities, and working conditions during remote work is crucial. The anticipated outcome is an impact on employee concentration, satisfaction, and performance during remote work, emphasizing management's pivotal role in optimizing remote work practices.